Self-defence against non-state actors: impulses from the Max Planck Trialogues on the Law of Peace and War - Christakis, Théodore; Corten, Olivier; Couzigou, Irène; Frowein, Jochen Abr.; Lo Giacco, Letizia; Grover, Leena; Hartwig, Matthias; Herik, Larissa J. van den; Kawagishi, Shin; Keinan, Guy; Oellers-Frahm, Karin; Österdahl, Inger; et al. (MPIL research paper series, 2017)
The legality of self-defence against non-state actors is currently one of the most contested issues of the jus contra bellum. How should we interpret state practice - has it already given rise, in law, to a broader concept of self-defence, or is the traditional state centred view still good law? Under which specific requirements should self-defence against non-state actors, if at all, be regarded as lawful and how can an abuse of an extended right to self-defence be prevented? The "Impulses from the Max Planck Trialogues on the Law of Peace and War" consist of short essays dealing with these questions